Analisis Pengaruh Promosi dan Harga Terhadap Keputusan Penggunaan Jasa Keuangan Shopee Paylater (Studi Kasus Pada Mahasiswa Mahasiswi FEB UMUS Brebes) - Amalia Siti Aisyah; Nur Afrida; Dwi Harini (Jurnal Riset dan Inovasi Manajemen, 2023)
The presence of paylater provides benefits for both the community and e-commerce players. People can meet their needs quickly, easily, and safely without having to worry about their cash flow. This feature can support the country's economic growth because more and more people are transacting more easily with this feature. This research was conducted at UMUS Brebes from March 2023 to July 2023. The population in this study was 1392 and for the sample of this study was 100 respondents. The testing tools and data analysis in this study use SPSS with testing and analysis methods through validity tests, reliability tests, classical assumption tests (normality tests, multicollinearity tests, heterokedasticity tests, t tests, F tests, Coefficient of Determination tests. The results in this study show that promotion has a significant effect on the decision to use, evidenced by the calculated t value for the variable X1 (7.407) greater than the table t (1.660). Price partially has no significant effect on the decision to use, this is evidenced by the calculated t value for the variable X2 (2.174) greater than the table t (1.660) but the significant value t X2 greater than 0.05 or 0.000 < 0.05. Promotion and Price have a significant effect on the decision to use, this result is shown by a significant value of 0.000 less than 0.05 and a calculated F value of 206.525 greater than F table 3.09. Promotion and Price were able to explain the dependent variable, namely Usage Decision by 81%, the remaining 19% was explained by other variables outside this study. These results show that promotions and prices simultaneously have a significant effect on variables tied to the decision to use Shopee Paylater.